2018
DOI: 10.1002/2017ja024272
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Observations of the Evolution of Polar Cap Arcs in Both Hemispheres

Abstract: We report results from the analysis of a case of conjugate polar cap arcs (PCAs) observed on 5 February 2006 in the Northern Hemisphere by the ground‐based Yellow River Station all‐sky imager (Svalbard) and in both hemispheres by the space‐based DMSP/SSUSI and TIMED/GUVI instruments. The PCA's motion in dawn‐dusk direction shows a clear dependence on the interplanetary magnetic field (IMF) By component and presents a clear asymmetry between Southern and Northern Hemispheres, that is, formed on the duskside and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 72 publications
4
35
0
Order By: Relevance
“…Using the particle data from the DMSP SSJ/4 spectrometer they showed the arcs to be associated with ion precipitation, consistent with formation on closed field lines. Xing et al () presented a similar observation with a conjugate PCA associated with ion precipitation in the DMSP particle data that was hence also consistent with a closed field line mechanism. DMSP particle data were also published in association with a large‐scale PCA in Fear et al ().…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Using the particle data from the DMSP SSJ/4 spectrometer they showed the arcs to be associated with ion precipitation, consistent with formation on closed field lines. Xing et al () presented a similar observation with a conjugate PCA associated with ion precipitation in the DMSP particle data that was hence also consistent with a closed field line mechanism. DMSP particle data were also published in association with a large‐scale PCA in Fear et al ().…”
Section: Introductionsupporting
confidence: 57%
“…Data from the particle spectrometer on board the DMSP spacecraft were obtained for events when the spacecraft track crossed the arc and were used to classify whether each event corresponded to open or closed field lines. If arcs are associated with an ion signature and seen in both hemispheres, then they are consistent with a closed field line formation mechanism (e.g., Carter et al, ; Xing et al, ). If the arcs are associated with an electron‐only signature, then they are consistent with an open field line mechanism (Newell et al, ; Reidy et al, ), whether they are seen in one or both hemispheres.…”
Section: Observationsmentioning
confidence: 87%
“…1.3 and 5.2). Carter et al (2017) and Xing et al (2018) presented separate SSUSI observations of polar cap arcs occurring simultaneously in both hemispheres that were found to be consistent with formation on closed field lines. In the case of Carter et al (2017), they showed two transpolar arcs occurring in both hemispheres simultaneously.…”
Section: Optical and In-situ Particle Signatures At Low-altitudementioning
confidence: 73%
“…used these data to suggest that there are three different formation mechanisms for polar cap arcs: two which occur on closed fields and one on open. Fear et al (2014), Carter et al (2017) and Xing et al (2018) presented DMSP particle observations, as well as observations from multiple ground-based and spacecraft instruments, of transpolar arcs occurring on closed field lines. The DMSP particle detector measured ion and electron precipitation associated with each of these arcs.…”
Section: Optical and In-situ Particle Signatures At Low-altitudementioning
confidence: 99%
See 1 more Smart Citation